Calcium handling maturation and adaptation to increased substrate stiffness in human iPSC-derived cardiomyocytes: The impact of full-length dystrophin deficiency - Pioner, Josè Manuel; Santini, Lorenzo; Palandri, Chiara; Langione, Marianna; Grandinetti, Bruno; Querceto, Silvia; Martella, Daniele; Mazzantini, Costanza; Scellini, Beatrice; Giammarino, Lucrezia; Lupi, Flavia; Mazzarotto, Francesco; et al. (Frontiers in Physiology, 2022)
Cardiomyocytes differentiated from induced pluripotent stem cells are a unique source for modelling inherited cardiomyopathies. In particular, the possibility of observing maturation processes in a simple culture dish opens novel perspectives in the study of early-disease defects caused by genetic mutations before the onset of clinical manifestations. For instance, calcium handling abnormalities are considered as a leading cause of cardiomyocyte dysfunction in several genetic-based dilated cardiomyopathies, including rare types such as Duchenne Muscular Dystrophy (DMD)-associated cardiomyopathy. To better define the maturation of calcium handling we simultaneously measured action potential and calcium transients using fluorescent indicators at specific time points. We combined micropatterned substrates with long-term cultures to improve maturation of hiPSC-CMs (60, 75 or 90 days post-differentiation). In control-(hiPSC)-CMs the increased contribution of the SR to Ca release (estimated by post-rest potentiation or Caffeine-induced Ca-Ts) appeared as the main determinant of the progressive rise of Ca-T amplitude during maturation. As an example of severe cardiomyopathy with early onset, we compared hiPSC-CMs generated from a DMD patient (DMD-ΔExon50) and a CRISPR-Cas9 genome edited cell line isogenic to the healthy control with deletion of a G base at position 263 of the DMD gene (c.263delG-CMs). In DMD-hiPSC-CMs, changes of Ca-transients during maturation were less pronounced: indeed, DMD cells at 90 days showed reduced CaT amplitude and faster Ca-T rise and RT50, as compared with hiPSC-CMs controls. Caffeine-CaT amplitude was reduced with slower CaT, suggesting lower SR calcium content and NCX function in DMD vs. control cells. Nonetheless, the inotropic and lusitropic responses to forskolin were preserved. CRISPR-induced C.263delG-CM line recapitulated the same developmental calcium handling alterations observed in DMD-CMs. We then tested the effects of micropatterned substrates with higher stiffness. In control hiPSC-CMs, higher stiffness leads to higher amplitude of Ca-T with faster decay kinetics. In hiPSC-CMs lacking full-length dystrophin, however, stiffer substrates did not modify Ca-Ts but only led to higher SR Ca content. These findings highlighted the inability of dystrophin-deficient cardiomyocytes to adjust their calcium homeostasis in response to increases of extracellular matrix stiffness, which suggest a mechanism occurring during the physiological and pathological development (i.e. fibrosis).